Therapeutic Management of an Outbreak of Pasteurellosis in Sheep and Goats in Karnatka: A Case Report - Kavitha, G.; Giridhara , P.; Byregowda , S.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
This work is licensed under the Creative Commons Attribution International License (http:// creativecommons.org/licenses /by/4.0/P), which permits unrestricted use, distribution and reproduction in any medium, provided the original work is properly cited. Copyright @: 2019 by authors and SVSBT.Pasteurellosis caused by Pasteurella multocida is an acute septicaemic disease characterized by high morbidity and mortality in cattle, sheep, goat and poultry resulting in severe economic losses. Hemorrhagic septicaemia is endemic in most parts of tropical Asia, Africa, and India and causes high mortality in livestock. Cattle and buffalo are the most common hosts, but pigs, sheep, goats, deer, and camels are also susceptible to infection and disease (Blackall et al., 2000). Vaccination with undefined, killed vaccines is practiced in areas where the disease is endemic and has reduced the incidence of disease, but the duration of immunity is short and significant outbreaks still occur (Verma and Jaiswal, 1998) and it is widely considered that buffaloes are the more susceptible. Although outbreaks of hemorrhagic septicaemia have been reported in sheep, goats and swine, it is not a frequent or significant disease. In India, the disease normally assumes endemic character just before and during the monsoon season. Transmission occurs by the inhalation or ingestion of the infected material.